Região e regionalização nos livros didáticos de geografia - Marinheiro, Dulcimara Lugoboni (2009)
This work intends to concern a reflection about the region and regionalization in the didact books. This, it s necessary to get the understand of the concept of region and contextualize it historically and geographically from national geographers. Support us Gomes (2003, 2006), Lencioni (1999, 2002), Corrêa (1986,2006) and Moreira (2008). In Classical Geography we point to two important concepts of geographic region for science geographic: the natural and geographic regions. We consider significant contributions of Classical Geography Lablacheana and we emphasize on the Critical Geography the materialism concepts. Two major concepts, born in New Geography we exposed: Homogeneous Region and Functional Region. In the relationship established with the productions of knowledge theory and practice we have as reference the analyzes of Didact Nation Textbook Plan 2008. Then we did a list of the collection displayed by most of teachers in São Bernardo do Campo city. This study observes that discussions about this topic start in sixth grade the sense attributed to it is administrative political unit or homogeneous regions. The works analyzed present, explicitly or implicitly, a definition of region. All authors sought is related to geographical science. However, although the intention was to do critical approach, it was in the form of approach of Classical Geography